Drawn in a peek into the inspiring sketchbooks of 44 fine artists, illustrators, graphic designers, and cartoonists - Rothman, Julia (Quarry Books, 2011)
"This book shares large full-color images and profiles each of the high-profile, amazingly talented artists that discuss their sketchbooks and how they use them. People are fascinated by artist's sketchbooks. They offer a glimpse into private pages where artists brainstorm, doodle, develop and work on ideas, and keep track of their musings. Artists use these journals to document their daily lives, produce their initial ideas for bigger projects, and practice their skills. Using a variety of media from paint to pencil to collage, these pages can become works of art themselves. They often feel fresh and alive because they are first thoughts and often not reworked. These pages capture the artist's personalities along with glimpses of their process of working and inspirations"--
Print version record
Keywords: Drawing; Notebooks; Dessin; Cahiers; drawing (image-making); notebooks; ART; Individual Artists; Artists' Books; CRAFTS & HOBBIES; General; ART; General